Economic Recovery of Calcium Phosphates From Swine Lagoon Sludge Using Quick Wash Process and Geotextile Filtration - Szogi, Ariel A.; Vanotti, Matias B.; Shumaker, Paul D. (Frontiers in Sustainable Food Systems, 2018)
To maintain the waste treatment capacity of anaerobic swine lagoons, excessive accumulation of sludge in the bottom of the lagoon is traditionally removed by dredging and pumping followed by dewatering prior to land application. A widespread and low-cost method of dewatering this lagoon sludge in U.S. farms is the use of geotextile bag filtration. Because of typically high phosphorus (P) contents in lagoon sludge, the dewatered sludge is eventually hauled to distant fields to reduce the environmental risk of excess P in land nearby the lagoon. The inclusion of a P recovery approach, called Quick Wash (QW), along with the geotextile bag technology could eliminate or reduce hauling costs of dewatered sludge and produce a valuable P product for use as fertilizer. The QW process uses a novel combination of acid, base, and organic polyelectrolytes to selectively extract and recover P from manure solids. The objective of this study was to evaluate the potential advantage and technical feasibility of combining the QW process and geotextile dewatering in a system to extract and recover P from lagoon sludge. Laboratory tests results showed that the amount of recoverable P from lagoon sludge depends on the pH level obtained by acidification. The highest release of P in solution, 83% of total initial P, was obtained when the lagoon sludge was acidified to pH 3. The amount of P recovered as a precipitate with lime addition at pH 10 was about 79% of the initial total P in the sludge. A mass flow balance confirmed that about 20% of the total P remained in the dewatered sludge solids. The effluent contained extremely low soluble P concentrations. The calcium phosphate product was identified as amorphous calcium phosphate (ACP) with very low heavy metal content. The recovered ACP had P grades (33.2–35.5% P2O5), higher than rock phosphate, with the advantage that there is no need for additional chemical processing for its use as fertilizer. Results of this study support the technical feasibility of using the QW process in combination with geotextile bag filtration for the economic recovery of P from anaerobic swine lagoons.